The Autobiographical Works of Valerius of Bierzo: their structure and purpose - Collins, Roger (Antigüedad y Cristianismo, 1986)
Of all the major literary figures of Visigothic Spain, Valerius is probably, at first sight, the oddest, certainly the least well understood, and the most unjustly vilified. Unlike the other principal writers of the period he has made no mark in contemporary records other than in his own works, which alone, for better or worse, can speak for him. (...)